Greening Energy tourist complexes - Ніколаєв, К.Д.; Білявський, Г.О.; Бабікова, К.О. (Proceedings of National Aviation University (archive), 2009)
Basic resource safety technologies and alternative energy are examined in this article, the use of which is possible in development of tourism industry